Anti-Oxidative Bioactivities of Medicinal Herbs in the Treatment of Aging-Related Diseases - Hye-Sun Lim; Gunhyuk Park; Yong-Ung Kim (MDPI AG, 2024)
Over the last 20 years, significant progress has been made in understanding the biology of aging and lifespans [...]